Homeostasis Disrupted and Restored—A Fresh Look at the Mechanism and Treatment of Obesity During COVID-19 - Dickey, Jacqueline; Davtyan, Camelia; Davtyan, David; Taegtmeyer, Heinrich (Frontiers in Cardiovascular Medicine, 2021)
The prevalence of obesity in the United States approaches half of the adult population. The COVID-19 pandemic endangers the health of obese individuals. In addition, the metabolic syndrome poses a challenge to the health of obese adults. Bariatric surgery and diet restore metabolic homeostasis in obese individuals; however, it is still unclear which strategy is most effective. For example, intermittent fasting improves insulin sensitivity and diet alone decreases visceral adipose tissue at a disproportionately high rate compared to weight loss. Bariatric surgery causes rapid remission of type 2 diabetes and increases incretins for long-term remission of insulin resistance before meaningful weight loss has occurred. Malabsorptive surgeries have provided insight into the mechanism of altering metabolic parameters, but strong evidence to determine the duration of their effects is yet to be established. When determining the best method of weight loss, metabolic parameters, target weight loss, and risk-benefit analysis must be considered carefully. In this review, we address the pros and cons for the optimal way to restore metabolic homeostasis.